TOC INDONESIAN JOURNAL OF LEGAL AND FORENSIC SCIENCES Volume 1 tahun 2017 - Wirasuta, gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 7 (2017): Indonesian Journal of Legal and Forensic Sciences, 2017)
INDONESIAN JOURNAL OF LEGAL AND FORENSIC SCIENCES Volume 1 tahun 2017